(untitled) (Research, Society and Development, 2021)
The Covid-19 pandemic led to an increase in the rate of psychophysical illness. As a result of the sanitary measures, the psychological assistance needed to be carried out virtually, through the so-called Telepsychology. Its use can be a reason for insecurity for many professionals who do not feel prepared to use it. This theoretical study was designed from the reading of national and international productions and aims to contribute by adding information that collaborates in the discussion about the practice of teaching and training psychologists in Brazil. We can conclude that the problem of psychological suffering resulting from the isolation measures taken to contain the Covid-19 pandemic led authorities to allow the use of Telepsychology in Brazil. The consultations are being carried out remotely, however, many doubts are still observed by therapists and clients regarding the use of technology. It should be noted that the issues discussed here aim to provide data for a better reflection on the training of the therapist and are fundamental for the future development of psychology, especially in Brazil.